KONSTRUKSI MAKNA RELIGIOKULTURAL DAN PELESTARIAN BUDAYA BATAK TOBA - Nova Simbolon; Harisan Boni Firmando; Roida Lumbantobing; Albiner Siagian; Martua Sihaloho (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study aims to analyze the construction of religio-cultural meaning and the HKBP Church's strategies in preserving and supervising Toba Batak cultural practices, particularly those related to death and the afterlife, at HKBP Bolon Resort Pangururan, Samosir Regency. Through a qualitative approach using in-depth interviews, observation, and documentation studies, this study found that Toba Batak customs remain an important part of the congregation's identity and continue to be preserved in various cultural practices. However, the meaning of these customs has been reconstructed by the church through a process of inculturation, so that they are no longer understood as magical rituals or forms of spirit worship, but rather as cultural expressions imbued with Christian values. The church implements a supervisory mechanism through the clergy. elders, and huria teachers to ensure that customs are carried out without deviating from God's word. This research also shows that the congregation accepts this new construction of meaning as a form of harmonization between customs and Christian faith, thus preserving the customs without losing their theological orientation. Thus, the HKBP plays a role not only as a religious institution but also as a cultural agent that reimagines the meaning of customs to align with Christian spirituality.